Circulating Normal IgG as Stimulator of Regulatory T Cells: Lessons from Intravenous Immunoglobulin. Issue 11 (November 2017) - Maddur, Mohan S; Kaveri, Srini V.; Bayry, Jagadeesh
Abstract : Intravenous immunoglobulin (IVIG), a pooled normal IgG formulation prepared from thousands of healthy donors' plasma, is extensively used for the immunotherapy of autoimmune and inflammatory disorders. Recent reports demonstrate that IVIG exerts anti-inflammatory actions by stimulating the activation and expansion of regulatory T (Treg) cells by multiple mechanisms via antigen-presenting cells (APCs).